2015
DOI: 10.1016/j.watres.2015.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Spoilt for choice: A critical review on the chemical and biological assessment of current wastewater treatment technologies

Abstract: The knowledge we have gained in recent years on the presence and effects of compounds discharged by wastewater treatment plants (WWTPs) brings us to a point where we must question the appropriateness of current water quality evaluation methodologies. An increasing number of anthropogenic chemicals is detected in treated wastewater and there is increasing evidence of adverse environmental effects related to WWTP discharges. It has thus become clear that new strategies are needed to assess overall quality of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
143
0
6

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(151 citation statements)
references
References 398 publications
2
143
0
6
Order By: Relevance
“…Traditionally, both chemical and biological treatments or a combination of them have been employed [3]. However, biological treatments have many advantages because they are cheaper, more reliable, can be done on site and their efficiency can be improved by the choice of a variety of microorganisms [4]. Bioremediation processes explore the use of biological mechanisms to destroy, transform or immobilize environmental contaminants…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, both chemical and biological treatments or a combination of them have been employed [3]. However, biological treatments have many advantages because they are cheaper, more reliable, can be done on site and their efficiency can be improved by the choice of a variety of microorganisms [4]. Bioremediation processes explore the use of biological mechanisms to destroy, transform or immobilize environmental contaminants…”
Section: Introductionmentioning
confidence: 99%
“…One of the results of their response is a change in light emission intensity depending on sample toxicity degree. Results from luminescent bacteria acute toxicity test proved to be a valuable tool for efficient wastewaters pollution control (Rodrigues and Umbuzeiro 2011;Kokkali and Delft 2014;Prasse et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Genotoxicity assessment is of great importance for public and environmental health; therefore, genotoxicity testing is among the most widely used bioassays in ecotoxicology (Prasse et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Inroads into understanding the transformation of antibiotics are being made by various researchers and it has been found that while most antibiotics lose their activity during water disinfection, a few do form biologically active transformation products (Dodd et al, 2009;Escher and Fenner, 2011;Mestankova et al, 2012;Keen and Linden, 2013). In addition to understanding the chemistry behind their transformation, various technologies are in development to effectively remove pharmaceuticals and their disinfection transformation products from wastewater (Prasse et al, 2015). These technologies are however in their infancy and have yet to be adopted widely in -first world countries‖, let alone in developing countries such as South Africa.…”
Section: Introductionmentioning
confidence: 99%